An effective research supervision management via a multi-agent system - Jassim O.A.; Mahmoud M.A.; Ahmad M.S. (Asian Research Publishing Network, 2023)
One of the challenges in research development is supervision management and its related activities. Inexperienced supervisors may have difficulties in recommending the appropriate research activities for their students and the students may not have the skills in research. Consequently, the main aim of this study is to develop a supervision management framework that incorporates a multi-agent system for managing research development. In developing the framework, the most important development stages are analyzed from the literature of research development process. The proposed framework consists of three phases which are Research Development Activities, Performance and Completion Measurement, and Tracking Activities. The components of the framework are discussed as possible implementation for a general application of research supervision management. The proposed framework is validated by 22 experts from Malaysian, Singaporean, and Jordanian universities. The validation results show that the proposed framework is useful to manage the supervision activities of research development. 2005 - 2016 JATIT & LLS. All rights reserved.